Ethical implications and decision making in care education process - Layse Kelle Silva; Paulo Roberto dos Santos Marins; Tábata Cerqueira Nascimento Nobre; Iracema da Silva Frazão; Darci de Oliveira Santa Rosa (Universidad de Antioquia, 2014)
Objective. To determine ethical implications for nursing practice at the point of decision making by nursing professors in practice area. Methodology. A qualitative method was adopted, with use of semistructured interviews with sixteen nursing professors who delivered care at a teaching hospital in Salvador, Bahia, from May to June 2011. The methodological reference used was the discourse of the collective subject (DCS) by Lefévre and Lefévre. Results. In response to DCSs, the following subjects appeared: "Ethics is fundamental and of vital importance in the decision making process," "searching for knowledge and research to identify problems and solutions, including alternatives and support for decisions," and "to act in the best way." Conclusion. Professors who provide education about patient care also delivered care. They have the responsibility to consider the ethical implications of decision making because they stimulate fundamental reflection and could positively influence future nursing professionals.